Seizures after flumazenil administration in a case of combined benzodiazepine and tricyclic antidepressant overdose (2004)
Flumazenil is a competitive inhibitor of the GABA receptor which effectively counteracts the effects of benzodiazepine overdose. It is considered to be safe, although infrequent adverse effects, including seizures, have been described. We present the case of a 30-year-old patient who was found in coma after taking an unknown amount of benzodiazepines and tricyclic antidepressants in an attempt to commit suicide After the administration of flumazenil, the patient suffered generalized tonic-clonic seizure. The patient was admitted to the ICU due to respiratory insufficiency secondary to broncoaspiration, with a satisfactory evolution after 48 hours. The risk factors for the development of seizure after flumazenil admisnistracion are discussed, recomendation for its safe use are suggested.